Learning Outcomes in Electric Vehicle Technology: Competency-Based Learning Management According to the TVET Curriculum - Poolkrajang, Akkarat; Papanai, Rinradee (Journal of Engineering Education Transformations, 2025)
Automotive technology is changing rapidly and will fully enter the electric vehicle industry in the future. The teaching and learning management that emphasizes learning outcomes in electric vehicle technology is important to prepare learners for future labor market needs. This will result in high-quality learning management, which in turn will yield high-quality results. This research uses a research and development model. The informants to study the components and develop the model include administrators and teachers, and the groups of informants to evaluate the model. The research instruments used were interview forms and opinion assessment forms. The research results found that the components of electric vehicle technology teaching and learning include teachers, students, professional content, learning plans, teaching in the electric vehicle technology field, preparation of teaching media and equipment, and evaluation of learning outcomes. There are three parts to teaching and learning management that focus on learning outcomes in the field of electric vehicle technology. Part 1 is getting ready for teaching and learning, Part 2 is planning teaching and learning activities, and Part 3 is constantly improving and evaluating the teaching and learning model that focuses on learning outcomes in the field of electric vehicle technology. The overall level of opinion is at the highest level. In summary, teaching and learning management emphasize quality learning outcomes and the development of students to have high competence to meet the needs of electric vehicle technology establishments in Thailand.